(untitled) (Bangladesh Journal of Botany, 2018)
The phosphoric acid modified walnut and peanut shell were prepared and applied for the removal of the blue-green alga (Microcystis aeruginosa Kütz.). Orthogonal experiment was used to optimize the modified condition. For the efficient removal, 0.05 g of the modified walnut and peanut shell was added into 50 ml of algal culture and kept standing for 4 hrs. This condition was found best and under which the removal rate of algae can be reached > 90%. At the same time, a comparison between unmodified walnut and peanut shell and modified walnut and peanut shell on the removal of M. aeruginosa cells showed that, unmodified walnut and peanut shell have a removal rate of 31.51 and 29.90%, respectively. On the other hand, the modified walnut and peanut shell showed a removal rate of 96.55 and 93.75%, respectively. Walnut and peanut shells modified with phosphoric acid enhanced the removal efficiency of M. aeruginosa cells. So, the modified walnut and peanut shell were considered as a potential algaecide with high efficiency of obnoxious algae removal from the environment safely.